Sistem Informasi Manajemen Energi untuk Meningkatkan Efisiensi dan Ketepatan Pengelolaan Konsumsi Energi di Bandara - Arsa, Daniel; Aulia, Yudriqul; Perdana, Yogi (Journal of Information System Research (JOSH), 2026)
Energy consumption recording (electricity, water, and fuel) at Sultan Thaha Airport Jambi currently relies on manual methods using spreadsheets. This process is prone to human error, data fragmentation, and hinders crucial energy efficiency analysis for airport operations. The need for data accuracy is becoming increasingly vital in line with the government's initiatives to tighten budget efficiency and drive digital transformation in public infrastructure. To support energy conservation policies and optimize operational costs, a more transparent and integrated monitoring system is required. This research aims to design and implement a web-based Energy Management Information System to address these challenges. Using the Waterfall development method, the system is built with a modern architecture utilizing React.js for a responsive interface, Express.js as the backend, and PostgreSQL for a scalable database management. Black Box testing results indicate that the system is valid and successfully provides an integrated solution through Dashboard Monitoring, Digital Input Validation, and centralized data reporting. The implementation of this system transforms energy governance from manual to digitally integrated, providing a solid foundation for airport management in making strategic decisions aligned with national budget efficiency and energy sustainability programs.